Tetanus Toxoid (TT) Injections as a Condition of Marriage Registration for Prospective Brides in the Maqashid Sharia Perspective - Laily Hidayati (JURNAL PENDIDIKAN IPS, 2024)
Marriage is a legal and sacred place to develop the life of mankind through its off spring, so it is only natural for prospective brides to prepare everything from mental, physical and material preparation before going further to the level of marriage. One of the requirements for marriage, especially for prospective brides, is stated in the Joint Instruction of the Director General of Islamic Public Guidance and Hajj Affairs of the Ministry of Religion and the Director General of Communicable Disease Eradication and Environmental Health of the Ministry of Health Number 02 of 1989 concerning tetanus toxoid immunization of prospective brides. In the perspective of maqasid sharia, Tetanus Toxoid (TT) vaccination injections are allowed for the benefit and good of mankind, whereas when viewed from the point of view of maslahat, this tetanus injection is very good for couples who want to get married. With the information that the bride-to-be has been injected with tetanus toxoid (TT) vaccination to minimize or prevent the outbreak of tetanus disease, one of which can be sourced at the first time of sexual intercourse which can tear the hymen in women, the hymen that is injured due to conjugal relations if there is no prior prevention through tetanus toxoid (TT) vaccination can result in the outbreak of tetanus disease which can be dangerous to life.